Availability, price, and affordability of diabetes mellitus and thyroid dysfunction medicines in South Wollo zone, Northeast Ethiopia - Solomon Ahmed Mohammed; Haile Yirga Mengesha; Abel Andualem; Elham Seid; Getnet Mengistu Assefa (BMC Health Services Research)
Abstract Background Diabetes mellitus and thyroid dysfunction are prevalent endocrine disorders that impose enormous burdens on patients and countries. However, access to essential medicines remains inadequate in many low-income countries. This study evaluated medications’ availability, price, and affordability for these conditions. Methods A cross-sectional study was conducted at health facilities in the South Wollo zone in 2022. Following World Health Organization (WHO)/Health Action International (HAI) guidelines, 34 medicines were evaluated across 60 medicine outlets. Data were collected using a standardized tool adapted from WHO/HAI. Availability was measured by the percentage of facilities where the medicines were in stock. Prices were reported as median prices and median price ratios (MPR). Affordability was assessed based on the number of days’ wages required for the lowest-paid government workers to cover the full course of therapy. Results The availability of lowest-priced generic (LPG) diabetes and thyroid dysfunction medicines in the public sector was 24.4% and 28.7%, respectively. In private pharmacies, availability was 26.3% for diabetes and 21% for thyroid dysfunction medicines. Median prices for LPG medicines were higher in private pharmacies than in public health facilities, with 81.81% showing a statistically significant difference (p < 0.05). In private pharmacies, the prices of LPG diabetes (5, 71.43%) and thyroid dysfunction medicines (5, 83.33%) exceeded the reference price. None of the LPG diabetes and thyroid dysfunction medicines were affordable in either setting. Conclusions The study revealed a very low availability of medicines and a financial burden on patients. Therefore, the government should improve the availability of these essential medicines and regulate their prices.